Stakeholder-defined scientific needs for coastal resilience decisions in the Northeast U.S. (August 2020) - Molino, Grace D.; Kenney, Melissa A.; Sutton-Grier, Ariana E.
Abstract: Over the past decade, coastal communities and ecosystems in the Northeast United States have begun to face acute and chronic impacts of climate change. Extreme events such as Superstorm Sandy caused stakeholders in this region to examine what information is needed to implement adaptation and mitigation plans to prepare for the next major storm. The objective of this study was to determine research needs identified by stakeholders in the Northeast needed for decision-support and policy creation so that scientists can target future research efforts to fill gaps. Modeled after document analysis methods in Dilling et al. (2014), this study examines documents sourced from local and regional organizations in both the public and private sectors to determine gaps in information necessary for climate resilience planning. Stakeholders throughout the Northeast expressed a need for solution-based research, in particular natural and nature-based solutions such as wetlands. Additionally, there was a need to better understand the economic impacts of climate change on key industries in the region as well as cost-benefit analyses of different adaptation options. It was also determined that government organizations, such as Sea Grant, play a crucial role in supporting stakeholder needs assessments both in terms of funding and providing necessary expertise. This study provides a baseline of stakeholder-expressed research needs in the Northeast to start the conversation between communities and researchers interested in conducting useable science. Highlights: A federal role in local resilience efforts is crucial for local voices to be heard. Adaptation of vulnerable infrastructure is top priority for communities. More research is needed on how and where to implement nature-based solutions. More evaluation of the economic costs of climate change to stakeholders is desired. Social science research needs to support resilience efforts were largely absent.